Degradation recycling and reapplication method of anhydride cured epoxy resin fiber reinforced composite material
Through the alkaline degradation solution treatment and dehydrated cyclic anhydride reaction, the fibers and curing agents in the epoxy resin fiber reinforced composite materials were successfully recovered and reused the acid anhydride curing, which solved the problem of difficult treatment of waste wind power blades and achieved efficient material recovery and recycling, reducing environmental pollution.
Patent Information
- Application Number
- CN202411244840.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art is difficult to effectively recycle and reuse acid anhydride to cure epoxy resin fiber reinforced composite materials, resulting in difficulty in handling waste wind power blades and environmental pollution.
The alkaline degradation solution is used to degrade the acid anhydride-cured epoxy resin fiber reinforced composite material. The recovered fiber, polyol and anhydride curing agent are separated out through filtration, extraction and dehydration ring anhydride reaction, and reused as additives and curing agents.
100% utilization of waste materials has been achieved, and the mechanical properties of recycled materials have no significant reduction compared with those of raw materials. It has good recycling potential and reduces the risk of environmental pollution.
Smart Images

Figure CN119119424A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of degradation of epoxy resin fiber reinforced composite materials, in particular to a degradation, recycling and re-application method of anhydride cured epoxy resin fiber reinforced composite material. Background Art
[0002] Vigorously develop the wind power industry, build a modern energy system, and promote the realization of the "carbon peak and carbon neutrality" goals. As the third largest source of electricity in my country, wind power generation has become an important part of the modern energy system. It is estimated that in the next 20 years, my country will produce nearly 3.7Mt of waste wind turbine blades. The main material in the blades is epoxy resin-based fiber-reinforced composite materials, which are mainly composed of glass fiber (GF) or carbon fiber (CF) materials and epoxy matrix. GF or CF materials have high production costs and are expensive, and have high recycling value, which also means that the degradation and recycling of waste blades has certain economic value. The interior of epoxy resin is a three-dimensional network cross-linked structure, which has the characteristics of insolubility, infusibility, and difficulty in biodegradation, which also makes the recycling of waste blades difficult.
[0003] At present, the common methods for treating waste blades are mainly: mechanical recycling, thermal energy recovery, and chemical recycling. Among them, the mechanical recycling method is to treat the waste blades by simple cutting, crushing, etc., and add the crushed fragments as fillers to materials such as concrete for use. The mechanical recycling method has a simple process and low construction difficulty, but it has high energy consumption and still poses a threat to the environment. The thermal energy recovery method is to treat it by incineration, high-temperature cracking, etc. The tail gas produced by the direct incineration method contains toxic gases, which will cause secondary pollution to the environment; the high-temperature cracking method can recover the fiber materials in the blades to a certain extent, and the recovery value has been improved, but the process is complicated, the energy consumption is high, and the processing cost is expensive. The chemical recovery method is to selectively cut the chemical bonds in the cross-linked structure of the resin through a chemical reaction, so that it changes from an insoluble and infusible cross-linked macromolecule to a small molecule compound that can be soluble in an organic solvent. While recovering high-value-added fiber materials, the degraded small molecule compounds can also be used as chemical raw materials, which greatly improves the recovery value of waste blades. Therefore, compared with mechanical recovery and thermal recovery, the chemical method is greener and more economical, and has great development potential in future large-scale industrial applications.
[0004] Therefore, in view of the above problems, the present invention urgently needs to provide a degradation, recycling and reuse method for anhydride-cured epoxy resin fiber-reinforced composite material. Summary of the invention
[0005] The purpose of the present invention is to provide a degradation, recycling and reuse method for anhydride-cured epoxy resin fiber-reinforced composite materials. The design of the degradation, recycling and reuse method for anhydride-cured epoxy resin fiber-reinforced composite materials solves the technical problem in the prior art that anhydride-cured epoxy resin fiber-reinforced composite materials cannot be recycled.
[0006] The present invention provides a degradation, recycling and reuse method for anhydride-cured epoxy resin fiber-reinforced composite material, which is characterized by comprising the following processing steps:
[0007] The anhydride-cured epoxy resin fiber-reinforced composite material is immersed in an alkaline degradation solution, degraded at a temperature of 40-180° C. for a reaction time of 4-20 hours, and after filtering and separation treatment, recovered fibers, solid-phase degradation products, and liquid-phase degradation products are obtained;
[0008] The liquid phase degradation product is concentrated, and the alcohol solvent is recovered, and then washed with water after concentration, and the oil phase is collected to obtain the recovered polyol, which can be used as an additive to replace part of the epoxy resin;
[0009] The solid phase degradation product is acidified with concentrated hydrochloric acid for 0.5-4h, and a carboxylic acid intermediate is obtained after extraction and concentration. The carboxylic acid intermediate is subjected to a dehydration cyclic anhydride reaction with a strong dehydrating agent at a reaction temperature of -10 to 40°C and in the presence of a catalyst for 1-24h. After the reaction is completed, the by-product is removed to obtain a recovered anhydride curing agent, which can be directly used as an epoxy resin curing agent;
[0010] The recycled polyol, epoxy resin and recycled acid anhydride curing agent are mixed in a certain proportion, and heated and cured to obtain the recycled epoxy resin.
[0011] Preferably, recycled polyol is used to replace epoxy resin, wherein the epoxy resin can be at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, aliphatic glycidyl ether epoxy resin, etc.; the amount of recycled polyol added is 0.1%-50% of the epoxy resin, wherein the molar ratio of epoxy resin to recycled anhydride curing agent is 1:(0.8-1.0).
[0012] Preferably, the mass ratio of the anhydride-cured epoxy resin fiber-reinforced composite material to the alkaline degradation liquid is 1:(2-20);
[0013] The alkaline degradation liquid contains alcohols and alkaline substances, and the mass ratio of the alkaline substances to the alcohol solvent is 1:(5-50).
[0014] Preferably, the alcohol comprises at least one of methanol, ethanol, isopropanol, n-propanol, n-butanol, ethylene glycol or glycerol;
[0015] The alkaline substance includes at least one of potassium hydroxide, sodium hydroxide, sodium carbonate, ammonia water, tetramethylammonium hydroxide or triethylamine.
[0016] Preferably, the degradation temperature is 40-180°C; the reaction time is 4-20h;
[0017] The solid phase degradation product is acidified with concentrated hydrochloric acid for 0.5-4h.
[0018] Preferably, the reaction temperature of the carboxylic acid intermediate and the strong dehydrating agent is -10 to 40°C; the reaction time is 1-24h; and the molar ratio of the carboxylic acid intermediate to the strong dehydrating agent is 1:(1-20).
[0019] Preferably, the strong dehydrating agent includes one of acetic anhydride, trifluoroacetic anhydride, di-tert-butyl dicarbonate and the like.
[0020] Preferably, the catalyst for the reaction of the carboxylic acid intermediate with the strong dehydrating agent includes one of 4-dimethylaminopyridine, magnesium chloride, magnesium iodide, titanium chloride, zinc chloride, cobalt chloride and the like.
[0021] Preferably, the molar ratio of the carboxylic acid intermediate to the catalyst is 1:(0.01-0.05).
[0022] Preferably, the anhydride-cured epoxy resin includes one of phthalic anhydride-cured epoxy resin, tetrahydrophthalic anhydride-cured epoxy resin, methyltetrahydrophthalic anhydride-cured epoxy resin, hexahydrophthalic anhydride-cured epoxy resin, methylhexahydrophthalic anhydride-cured epoxy resin, methylnadic anhydride-cured epoxy resin, pyromellitic dianhydride-cured epoxy resin or maleic anhydride-cured epoxy resin.
[0023] The degradation, recycling and reuse method of anhydride-cured epoxy resin fiber-reinforced composite material provided by the present invention has the following improvements compared with the prior art:
[0024] The degradation, recycling and re-application method of anhydride-cured epoxy resin fiber-reinforced composite material provided by the present invention comprises the following steps: degrading the anhydride-cured epoxy resin fiber-reinforced composite material by using an alkaline substance and an alcohol solvent to synergistically degrade the anhydride-cured epoxy resin fiber-reinforced composite material, filtering and separating the degradation product, washing, dehydrating and cycloanhydrification reaction, etc., separating the recovered fiber, the recovered anhydride curing agent and the recovered polyol, wherein the recovered anhydride curing agent can be directly used as an epoxy resin curing agent for reuse, and the recovered polyol compound can be directly used as an additive to replace part of the epoxy resin. The treated product can be directly recycled, achieving 100% utilization of the degradation product, and after curing with the recycled material, the mechanical properties thereof are not significantly reduced compared with the original anhydride-cured epoxy resin, showing good mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 is the infrared spectrum of the recovered anhydride curing agent described in the present invention;
[0027] Figure 2 is the nuclear magnetic hydrogen spectrum of the recovered anhydride curing agent described in the present invention;
[0028] Figure 3 is the infrared spectrum of the recovered polyol described in the present invention;
[0029] Figure 4 is the nuclear magnetic hydrogen spectrum of the recovered polyol described in the present invention;
[0030] Figure 5 This is an appearance diagram of the recycled epoxy resin described in the present invention. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The present invention provides a degradation, recycling and reuse method for anhydride-cured epoxy resin fiber-reinforced composite material, comprising the following processing steps:
[0033] S1) immersing the anhydride-cured epoxy resin fiber-reinforced composite material in an alkaline degradation solution, degrading it at a temperature of 40-180° C. for a reaction time of 4-20 hours, and obtaining recycled fibers, solid-phase degradation products, and liquid-phase degradation products after filtering and separation treatment;
[0034] S2) concentrating the liquid phase degradation product and recovering the alcohol solvent, washing with water after concentration, collecting the oil phase, and obtaining the recovered polyol, which can be used as an additive to replace part of the epoxy resin;
[0035] S3) the solid phase degradation product is acidified with concentrated hydrochloric acid for 0.5-4h, and a carboxylic acid intermediate is obtained after extraction and concentration, and the carboxylic acid intermediate is subjected to a dehydration cyclic anhydride reaction with a strong dehydrating agent at a reaction temperature of -10 to 40°C and in the presence of a catalyst for 1-24h. After the reaction is completed, the by-product is removed to obtain a recovered anhydride curing agent, which can be directly used as an epoxy resin curing agent;
[0036] S4) mixing the recovered polyol, epoxy resin and recovered acid anhydride curing agent in a certain proportion, and heating and curing to obtain the recovered epoxy resin.
[0037] Specifically, recycled polyols are used to replace epoxy resins, wherein the epoxy resin can be at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, aliphatic glycidyl ether epoxy resin, etc., wherein the amount of recycled polyol added is 0.1%-50% of the epoxy resin, wherein the molar ratio of epoxy resin to recycled anhydride curing agent is 1:(0.8-1.0).
[0038] Specifically, the mass ratio of the anhydride-cured epoxy resin fiber-reinforced composite material to the alkaline degradation liquid is 1:(2-20);
[0039] The alkaline degradation liquid contains alcohols and alkaline substances, and the mass ratio of the alkaline substances to the alcohol solvent is 1:(5-50).
[0040] Specifically, the alcohol includes at least one of methanol, ethanol, isopropanol, n-propanol, n-butanol, ethylene glycol or glycerol;
[0041] The alkaline substance includes at least one of potassium hydroxide, sodium hydroxide, sodium carbonate, ammonia water, tetramethylammonium hydroxide or triethylamine.
[0042] Specifically, the degradation temperature is 40-180°C; the reaction time is 4-20h;
[0043] The solid phase degradation product is acidified with concentrated hydrochloric acid for 0.5-4h.
[0044] Specifically, the reaction temperature of the carboxylic acid intermediate and the strong dehydrating agent is -10 to 40°C; the reaction time is 1-24h; and the molar ratio of the carboxylic acid intermediate to the strong dehydrating agent is 1:(1-20).
[0045] Specifically, the strong dehydrating agent includes one of acetic anhydride, trifluoroacetic anhydride, di-tert-butyl dicarbonate, and the like.
[0046] Specifically, the catalyst for the reaction of the carboxylic acid intermediate with the strong dehydrating agent includes one of 4-dimethylaminopyridine, magnesium chloride, magnesium iodide, titanium chloride, zinc chloride, cobalt chloride and the like.
[0047] Specifically, the molar ratio of the carboxylic acid intermediate to the catalyst is 1:(0.01-0.05).
[0048] Specifically, the anhydride-cured epoxy resin includes one of phthalic anhydride-cured epoxy resin, tetrahydrophthalic anhydride-cured epoxy resin, methyltetrahydrophthalic anhydride-cured epoxy resin, hexahydrophthalic anhydride-cured epoxy resin, methylhexahydrophthalic anhydride-cured epoxy resin, methylnadic anhydride-cured epoxy resin, pyromellitic dianhydride-cured epoxy resin or maleic anhydride-cured epoxy resin.
[0049] Embodiment 1
[0050] The degradation, recycling and reuse method of the anhydride-cured epoxy resin fiber-reinforced composite material provided in this embodiment includes the following processing steps:
[0051] 101) 2 parts of sodium hydroxide are completely dissolved in 100 parts of ethanol as a degradation solution, 10 parts of methyltetrahydrophthalic anhydride cured epoxy resin fiber reinforced composite material are immersed in the degradation solution, and the degradation reaction is carried out at a reaction temperature of 100° C. for 16 hours, and the resin matrix is completely degraded. After separation, recycled fibers, solid phase degradation products and liquid phase degradation products are obtained;
[0052] 102) concentrating the liquid phase degradation product and recovering ethanol, washing with water after concentration, collecting the oil phase, and obtaining recovered polyols with a yield of 95%, which can be directly used as an additive to replace part of the epoxy resin;
[0053] 103) The solid phase degradation product was acidified with concentrated hydrochloric acid for 4 hours, and a carboxylic acid intermediate was obtained after extraction and concentration. The carboxylic acid intermediate, trifluoroacetic anhydride and magnesium chloride were added in a molar ratio of 1:10:0.01 at a reaction temperature of 40°C for 1 hour for dehydration cyclic anhydride reaction. After the reaction, the by-products were removed to obtain a recovered anhydride curing agent with a yield of 86%, which can be directly used as an epoxy resin curing agent.
[0054] 104) 10 parts of recycled polyol, 90 parts of bisphenol A epoxy resin, 90 parts of recycled acid anhydride curing agent, and 0.9 parts of 1-methylimidazole were mixed, and cured according to a curing system of curing at 90°C for 1 hour, curing at 140°C for 1 hour, and curing at 160°C for 1 hour to obtain a recycled epoxy resin, whose mechanical properties are shown in Table 1.
[0055] Figure 1 The infrared spectrum of the anhydride curing agent recovered in this example is compared with the infrared spectrum of commercially available methyltetrahydrophthalic anhydride. The infrared characteristic peaks are completely consistent, 1768cm -1A strong characteristic peak of anhydride group appears at the bottom, which proves that the recovered anhydride curing agent has the same structure as the commercially available anhydride curing agent methyltetrahydrophthalic anhydride. Through the degradation and recycling method of the present invention, the waste epoxy resin with no economic value can be successfully converted back to raw materials, and the anhydride curing agent finished product with high economic value that is almost the same as the commercially available product can be obtained.
[0056] Figure 2 The H-NMR spectrum of the acid anhydride curing agent recovered in this example was used. A compound structure simulation analysis was performed based on the spectrum data, which was consistent with the results of infrared spectrum analysis, further proving that the recovered acid anhydride curing agent obtained was methyltetrahydrophthalic anhydride and had a high purity.
[0057] Therefore, the recovered acid anhydride curing agent of this embodiment can be used as the epoxy resin curing agent instead of methyltetrahydrophthalic anhydride.
[0058] Figure 3 The infrared spectrum of the recovered polyol in this example is as follows. Compared with bisphenol A epoxy resin, the -1 and 1100cm -1 A strong hydroxyl characteristic peak appeared at 1606cm -1 、1581cm -1 、1508cm -1 、1459cm -1 The characteristic peak of the benzene ring skeleton vibration at 826cm -1 The characteristic peak of the disubstituted benzene ring at the para position proves that the degradation product is consistent with bisphenol A epoxy resin in molecular skeleton structure. -1 No characteristic peak of epoxy group was found. Therefore, it can be proved that the recovered polyol obtained by the method of the present invention is a bisphenol A polyol compound rich in hydroxyl groups formed after the ester bond is broken.
[0059] Figure 4 This is the H-NMR spectrum of the recovered polyol of this example. A compound structure simulation analysis was performed based on the spectrum data, which was consistent with the infrared spectrum analysis result, further proving that the main component of the recovered polyol is bisphenol A polyol compound.
[0060] Therefore, the polyol compound can be used to replace part of the epoxy resin monomer.
[0061] By analyzing the structure of the recovered anhydride curing agent and the recovered polyols through infrared spectroscopy and nuclear magnetic hydrogen spectroscopy, it can be determined that during the degradation process, the ester bonds in the resin matrix are selectively broken, and the basic skeleton structure of the resin monomer and the anhydride curing agent is completely retained. Through post-treatment, the anhydride curing agent and the polyol are successfully separated, and both have high purity and can be directly used for the curing of epoxy resins, achieving 100% closed-loop recycling of anhydride-cured epoxy resin fiber-reinforced materials.
[0062] Embodiment 2
[0063] The degradation, recycling and reuse method of the anhydride-cured epoxy resin fiber-reinforced composite material provided in this embodiment includes the following processing steps:
[0064] 201) 4 parts of sodium hydroxide are completely dissolved in 80 parts of ethanol as a degradation solution, 10 parts of methyltetrahydrophthalic anhydride cured epoxy resin fiber reinforced composite material are immersed in the degradation solution, and the degradation reaction is carried out at a reaction temperature of 120° C. for 12 hours, and the resin matrix is completely degraded. After separation, the recycled fiber, solid phase degradation product and liquid phase degradation product are obtained;
[0065] 202) concentrating the liquid phase degradation product and recovering ethanol, washing with water after concentration, collecting the oil phase, and obtaining the recovered polyol with a yield of 96%, which can be directly used as an additive to replace part of the epoxy resin;
[0066] 203) The solid phase degradation product is acidified with concentrated hydrochloric acid for 4 hours, and a carboxylic acid intermediate is obtained after extraction and concentration. The carboxylic acid intermediate, di-tert-butyl dicarbonate and magnesium chloride are added in a molar ratio of 1:10:0.05 at a reaction temperature of 40°C for 20 hours for dehydration cyclic anhydride reaction. After the reaction is completed, the by-products are removed to obtain a recovered anhydride curing agent with a yield of 80%, which can be directly used as an epoxy resin curing agent;
[0067] 204) 20 parts of recycled polyol, 80 parts of bisphenol F epoxy resin, 90 parts of recycled acid anhydride curing agent, and 0.9 parts of 1-methylimidazole were mixed, and cured according to a curing system of curing at 90°C for 1 hour, curing at 140°C for 1 hour, and curing at 160°C for 1 hour to obtain a recycled epoxy resin, whose mechanical properties are shown in Table 1.
[0068] Embodiment 3
[0069] The degradation, recycling and reuse method of the anhydride-cured epoxy resin fiber-reinforced composite material provided in this embodiment includes the following processing steps:
[0070] 301) 8 parts of potassium hydroxide are completely dissolved in 160 parts of n-propanol as a degradation solution, 10 parts of methyltetrahydrophthalic anhydride cured epoxy resin fiber reinforced composite material are immersed in the degradation solution, and the degradation reaction is carried out at a reaction temperature of 150°C for 8 hours, and the resin matrix is completely degraded. After separation, the recycled fiber, solid phase degradation product and liquid phase degradation product are obtained;
[0071] 302) concentrating the liquid phase degradation product and recovering ethanol, washing with water after concentration, collecting the oil phase, and obtaining the recovered polyol with a yield of 93%, which can be directly used as an additive to replace part of the epoxy resin;
[0072] 303) The solid phase degradation product is acidified with concentrated hydrochloric acid for 1 hour, and a carboxylic acid intermediate is obtained after extraction and concentration. The carboxylic acid intermediate, acetic anhydride and magnesium chloride are added in a molar ratio of 1:5:0 at a reaction temperature of 20°C for 24 hours for dehydration cyclic anhydride reaction. After the reaction is completed, the by-products are removed to obtain a recovered anhydride curing agent with a yield of 72%, which can be directly used as an epoxy resin curing agent;
[0073] 304) 15 parts of recycled polyol, 45 parts of bisphenol A epoxy resin, 40 parts of aliphatic glycidyl ether epoxy resin, 90 parts of recycled acid anhydride curing agent, and 0.9 parts of 1-methylimidazole were mixed, and cured according to a curing system of curing at 90°C for 1 hour, curing at 140°C for 1 hour, and curing at 160°C for 1 hour to obtain a recycled epoxy resin, whose mechanical properties are shown in Table 1.
[0074] Embodiment 4
[0075] The degradation, recycling and reuse method of the anhydride-cured epoxy resin fiber-reinforced composite material provided in this embodiment includes the following processing steps:
[0076] 401) 8 parts of sodium carbonate are completely dissolved in 200 parts of methanol as a degradation solution, 10 parts of methyltetrahydrophthalic anhydride cured epoxy resin fiber reinforced composite material are immersed in the degradation solution, and the degradation reaction is carried out at a reaction temperature of 80°C for 20 hours, and the resin matrix is completely degraded. After separation, the recycled fiber, solid phase degradation product and liquid phase degradation product are obtained;
[0077] 402) concentrating the liquid phase degradation product and recovering ethanol, washing with water after concentration, collecting the oil phase, and obtaining recovered polyols with a yield of 91%, which can be directly used as an additive to replace part of the epoxy resin;
[0078] 403) The solid phase degradation product is acidified with concentrated hydrochloric acid for 4 hours, and a carboxylic acid intermediate is obtained after extraction and concentration. The carboxylic acid intermediate, trifluoroacetic anhydride and 4-2-methylaminopyridine are added in a molar ratio of 1:20:0.05 at a reaction temperature of 40°C for 1 hour for dehydration cyclic anhydride reaction. After the reaction is completed, the by-products are removed to obtain a recovered anhydride curing agent with a yield of 88%, which can be directly used as an epoxy resin curing agent;
[0079] 404) 50 parts of recycled polyol, 50 parts of bisphenol A epoxy resin, 90 parts of recycled acid anhydride curing agent, and 0.9 parts of 1-methylimidazole were mixed, and cured according to a curing system of curing at 90°C for 1 hour, curing at 140°C for 1 hour, and curing at 160°C for 1 hour to obtain a recycled epoxy resin, whose mechanical properties are shown in Table 1.
[0080] Comparative Example 1
[0081] The degradation, recycling and reuse method of the anhydride-cured epoxy resin fiber-reinforced composite material provided in this embodiment includes the following processing steps:
[0082] 100 parts of bisphenol A epoxy resin, 90 parts of methyltetrahydrophthalic anhydride curing agent, and 0.9 parts of 1-methylimidazole were mixed and cured according to a curing system of curing at 90°C for 1 hour, curing at 140°C for 1 hour, and curing at 160°C for 1 hour to obtain an epoxy resin, whose mechanical properties are shown in Table 1.
[0083] In Examples 1 to 4, recycled acid anhydride curing agent and polyol are used to partially replace epoxy resin and mixed with epoxy resin to prepare recycled epoxy resin. Compared with the material obtained in Comparative Example 1, the recycled epoxy resin can still show excellent mechanical properties, which are close to the performance of Comparative Example 1. Therefore, the resin matrix material recovered by this method is fully qualified for reuse and has excellent mechanical properties.
[0084] Table 1 Mechanical properties test results of comparative example cured epoxy resin and example re-cured epoxy resin
[0085] Test items Comparative Example 1 Embodiment 1 Embodiment 2 Embodiment 3 Embodiment 4 Tensile strength / MPa 60.54 59.69 56.01 58.34 55.52 Tensile modulus / GPa 2.65 2.67 2.65 2.58 2.56 Elongation at break / % 3.0 3.21 2.65 2.89 2.63 Bending strength / MPa 107.10 89.73 99.60 93.46 87.23 Flexural modulus / GPa 3.45 2.78 2.75 2.81 2.68
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for degradation, recycling and reuse of anhydride-cured epoxy resin fiber-reinforced composite materials, characterized in that: The processing steps include: The anhydride-cured epoxy resin fiber-reinforced composite material is immersed in an alkaline degradation solution, degraded at a temperature of 40-180° C. for a reaction time of 4-20 hours, and after filtering and separation treatment, recovered fibers, solid-phase degradation products, and liquid-phase degradation products are obtained; The liquid phase degradation product is concentrated, and the alcohol solvent is recovered, and then washed with water after concentration, and the oil phase is collected to obtain the recovered polyol, which can be used as an additive to replace part of the epoxy resin; The solid phase degradation product is acidified with concentrated hydrochloric acid for 0.5-4h, and a carboxylic acid intermediate is obtained after extraction and concentration. The carboxylic acid intermediate is subjected to a dehydration cyclic anhydride reaction with a strong dehydrating agent at a reaction temperature of -10 to 40°C and in the presence of a catalyst for 1-24h. After the reaction is completed, the by-product is removed to obtain a recovered anhydride curing agent, which can be directly used as an epoxy resin curing agent; The recycled polyol, epoxy resin and recycled acid anhydride curing agent are mixed in a certain proportion, and heated and cured to obtain the recycled epoxy resin.
2. The degradation, recycling and reuse method of anhydride-cured epoxy resin fiber-reinforced composite material according to claim 1, characterized in that: Recycled polyols are used to replace epoxy resins, wherein the epoxy resin can be at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, aliphatic glycidyl ether epoxy resin, etc.; the amount of the recycled polyol added is 0.1%-50% of the epoxy resin, wherein the molar ratio of the epoxy resin to the recycled anhydride curing agent is 1:(0.8-1.0).
3. The degradation, recycling and reuse method of anhydride-cured epoxy resin fiber-reinforced composite material according to claim 1, characterized in that: The mass ratio of the anhydride cured epoxy resin fiber reinforced composite material to the alkaline degradation liquid is 1:(2-20); The alkaline degradation liquid contains alcohols and alkaline substances, and the mass ratio of the alkaline substances to the alcohol solvent is 1:(5-50).
4. The degradation, recycling and reuse method of anhydride-cured epoxy resin fiber-reinforced composite material according to claim 3, characterized in that: The alcohol includes at least one of methanol, ethanol, isopropanol, n-propanol, n-butanol, ethylene glycol or glycerol; The alkaline substance includes at least one of potassium hydroxide, sodium hydroxide, sodium carbonate, ammonia water, tetramethylammonium hydroxide or triethylamine.
5. The degradation, recycling and reuse method of anhydride-cured epoxy resin fiber-reinforced composite material according to claim 2, characterized in that: The degradation temperature is 40-180°C; the reaction time is 4-20h; The solid phase degradation product is acidified with concentrated hydrochloric acid for 0.5-4h.
6. The degradation, recycling and reuse method of anhydride-cured epoxy resin fiber-reinforced composite material according to claim 1, characterized in that: The reaction temperature of the carboxylic acid intermediate and the strong dehydrating agent is -10 to 40°C; the reaction time is 1 to 24 hours; and the molar ratio of the carboxylic acid intermediate to the strong dehydrating agent is 1:(1-20).
7. The degradation, recycling and reuse method of anhydride-cured epoxy resin fiber-reinforced composite material according to claim 1, characterized in that: The strong dehydrating agent includes one of acetic anhydride, trifluoroacetic anhydride, di-tert-butyl dicarbonate and the like.
8. The degradation, recycling and reuse method of anhydride-cured epoxy resin fiber-reinforced composite material according to claim 1, characterized in that: The catalyst for the reaction of the carboxylic acid intermediate with the strong dehydrating agent includes one of 4-dimethylaminopyridine, magnesium chloride, magnesium iodide, titanium chloride, zinc chloride, cobalt chloride and the like.
9. The degradation, recycling and reuse method of anhydride-cured epoxy resin fiber-reinforced composite material according to claim 1, characterized in that: The molar ratio of the carboxylic acid intermediate to the catalyst is 1:(0.01-0.05).
10. The degradation, recycling and reuse method of anhydride-cured epoxy resin fiber-reinforced composite material according to claim 1, characterized in that: The anhydride-cured epoxy resin includes one of phthalic anhydride-cured epoxy resin, tetrahydrophthalic anhydride-cured epoxy resin, methyltetrahydrophthalic anhydride-cured epoxy resin, hexahydrophthalic anhydride-cured epoxy resin, methylhexahydrophthalic anhydride-cured epoxy resin, methylnadic anhydride-cured epoxy resin, pyromellitic dianhydride-cured epoxy resin or maleic anhydride-cured epoxy resin.
Citation Information
Cited By
Method for efficiently degrading and recycling waste epoxy resin and composite material thereof under catalysis of metal functionalized ionic liquid
CN120137261A
A method for efficient degradation and recovery of waste epoxy resin and composite materials thereof by metal-functionalized ionic liquid catalysis
CN120137261B
Degradation, recovery and regeneration method of degradable anhydride cured epoxy resin
CN120987797A
